Research on green light compensation model for emergency preemption in C-V2X environment - Changlong ZHANG; Farong HAN; Jimin WEI; Jingang DAI; Xiaodong YANG; Shibo QU (Dianxin kexue)
To reduce the impact of the emergency vehicle preemption strategy on vehicles in non-priority phases at intersections, an emergency preemption green light compensation model in C-V2X environment was proposed.The proposed model doesn’t affect the emergency vehicle preemption strategy.The green time of the non-priority phases was calculated according to the real-time traffic demand to minimize the adverse impact on vehicles in non-priority phases.The proposed model was verified with simulation using an emergency vehicle.The results demonstrate that the proposed method can effectively decrease the queue lengths and reduce the average delay in non-priority phases after applying the emergency vehicle preemption strategy.The proposed method can improve traffic efficiency by optimizing the signal timing after the emergency vehicle passes through an intersection.